Response of prehistoric human activity to environmental changes since 7, 000 cal yr BP in Nenjiang River Basin, northeast China. (25th February 2019) - Leng, Chengcheng; Tang, Zhuowei; Zhang, Wei; Jie, Dongmei; Wang, Hainan; Gao, Guizai; Li, Dehui; Li, Nannan; Wang, Jiangyong; Shi, Jichen; Liu, Baojian; Liu, Xu; et al.
Abstract: Many prehistoric cultural sites with distinctive regional characteristics have been discovered on fixed aeolian dunes in Nenjiang River Basin, Northeast China. The rise and decline of these cultures was substantially influenced by the regional environmental evolution. To elucidate how human activity responded to environmental changes, we conducted analyses of phytoliths, grain-size and organic content of a natural sediment profile at Honghe Neolithic site. The phytolith analysis shows that the vegetation was dominated by C3 Pooideae, and the grain-size analysis shows that the site was strongly affected by the winter monsoon and that the sediment source was regionally-derived aeolian sand from Songnen Sandy Land. The environment of Nenjiang River Basin experienced several periods of sand dune mobilization and stabilization: During 7024-4233 cal yr BP, 3414-2433 cal yr BP and 1700-1000 cal yr BP the dunes of Songnen Sandy Land were stable and the environment was warm and wet. During 4233-3, 414 cal yr BP, 2433-1, 700 cal yr BP and 1000 cal yr BP-present the dunes were mobile and the climate was cold and dry. In addition, the global 4.2 ka cold climatic event is recorded in the section. Correspondingly, the human history can be divided into three periods: (I) Neolithic Age (7024-4, 233 cal yr BP ) when the winter monsoon was weak, the sand dunes were stable and the environment was warm and wet. Human activity was relatively intense during this period, manifested by the Angangxi Culture in the middle reaches of Nenjiang River, a representative of the 'Fishing-Hunting Neolithic Culture'. However, only a small number of tombs post-dating 4200 cal yr BP have been found in the Angangxi district (II) Bronze Age (4233-2, 433 cal yr BP ). The Xiaolaha Cultural sites in the lower reaches of Nenjiang River, which inherited the characteristics of the Angangxi Culture, flourished during 3800-3260 cal yr BP, and after a transitional period it gradually evolved into the Baijinbao Culture (2800-2, 500 cal yr BP). This pattern of evolution shows that human activity diminished in the middle reaches of Nenjiang River after 4233 cal yr BP, in response to the colder and drier environment. (III) Post-Warring States period (2 433 cal yr BP - present). The Hanshu II culture prospered during 2380-2067 cal yr BP, and the Hongmashan Culture was the dominant culture during 2000-1700 cal yr BP. Historical documents and archaeological evidence revealed that frequent wars interrupted the continuity of human cultural development after 2000 cal yr BP in the Nenjiang River Basin.